2022
DOI: 10.3390/ma15051632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al Addition on Grain Refinement and Phase Transformation of the Mg-Gd-Y-Zn-Mn Alloy Containing LPSO Phase

Abstract: The effect of 0–1.0 at.% Al additions on grain refinement and phase transformation of the Mg-2.0Gd-1.2Y-0.5Zn-0.2Mn (at.%) alloy containing a long period stacking ordered (LPSO) phase was investigated in this work. The addition of Al promoted the formation of the Al2RE phase in the Mg-2.0Gd-1.2Y-0.5Zn-0.2Mn (at.%) alloy, and the dominant secondary phases in the as-cast Mg-2.0Gd-1.2Y-0.5Zn-0.2Mn-1.0Al (at.%) alloy were the Mg3RE phase, LPSO phase, and Al2RE phase. With increased Al addition, the area fraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Gibbs free energy difference between Al and RE is the smallest in Mg-RE-Al alloys [33], so Al and RE react preferentially, which leads to the formation of granular Al 2 RE during solidification process of GW9411 alloy [16]. The lower cooling rate, the smaller the nucleation driving force of granular Al 2 RE [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibbs free energy difference between Al and RE is the smallest in Mg-RE-Al alloys [33], so Al and RE react preferentially, which leads to the formation of granular Al 2 RE during solidification process of GW9411 alloy [16]. The lower cooling rate, the smaller the nucleation driving force of granular Al 2 RE [26].…”
Section: Discussionmentioning
confidence: 99%
“…In industrial production, gravity casting is an important way to prepare components with complex geometric dimensions. The grain size of casting alloys is quite coarse, and Zr is often used as a refiner [13,14], which is usually added in form of Mg-Zr intermediate alloy, but Zr refinement has the disadvantage of high cost and low utilisation [15,16]. These limit its extensive application.…”
Section: Introductionmentioning
confidence: 99%
“…Mg alloys are the lightest metallic structural materials with superior properties, such as excellent castability, good damping capacity, and high specific strength, making them ideal light-weight materials for applications in many industrial fields including automobiles and rail traffic [ 1 , 2 , 3 , 4 , 5 ]. It has been reported that every weight reduction of 100 Kg of a vehicle reduces the fuel consumption by 0.3–0.4 L/100 km [ 6 ].…”
Section: Introductionmentioning
confidence: 99%